Consumers’ Attitude and Preference toward Fresh Tomatoes in Special Region of Yogyakarta, Indonesia - Yolanda, Gity Maulina; Darwanto, Dwidjono Hadi; Ardhi, M. Khalifatul (AGRARIS: Journal of Agribusiness and Rural Development Research, 2022)
Increasing tomatoes consumption which is driven by needs and desires, changes consumers’ tastes and preferences. This study aimed to determine consumers’ attitudes and preferences towards tomato’s attributes. A convenience sampling which consisted of 150 respondents in the Special Region of Yogyakarta was selected for this research. Fishbein’s Multi-attribute was used to analyze consumers’ attitude, and a conjoint analysis was employed to identify consumers’ preferences. According to the findings of this study, consumers have a favorable attitude toward tomato attributes such as freshness, color, firm texture, surface appearance, and taste. Meanwhile, the findings of the conjoint analysis revealed that the color of the tomatoes was the most favored characteristic. The most preferred combination of tomato characteristics was red color, highly fresh, firm texture, spot-free surface look, and sweetness.